"Peri‐Implantitis": A Complication of a Foreign Body or a Man‐Made "Disease". Facts and Fiction. (30th May 2016) - Albrektsson, Tomas; Canullo, Luigi; Cochran, David; De Bruyn, Hugo
Abstract: Background: The discrepancy between some scientific views and the daily clinical experience with dental implants has made the topic of "periimplantitis" highly controversial, especially the discussion whether "periimplantitis" should even be considered a "disease" or whether marginal bone loss instead would represent a complication of having a foreign body placed in the oral cavity. Purpose: The aim of the present paper was to present the outcomes from a consensus meeting on "peri‐implantitis" in Rome, Italy (January 8–10, 2016). Materials and Methods: Seventeen clinical scientists were invited to, based on prepared reviews of the literature, discuss topics related to "periimplantitis." Results and conclusions: Oral implants may lose bone or even display clinical failure. However, progressive bone loss threatening implant survival is rare and limited to a percent or two of all implants followed up over 10 years or more, provided that controlled implant systems are being used by properly trained clinicians. There is very little evidence pointing to implants suffering from a defined disease entity entitled "peri‐implantitis." Marginal bone loss around implants is in the great majority of cases associated with immune‐osteolytic reactions. Complicating factors include patient genetic disorders, patient smoking, cement or impression material remnants in the peri‐implant sulcus, bacterial contamination of the implant components and technical issues such as loose screws, mobile components or fractured materials. These reactions combine to result in cellular responses with the end result being a shift in the delicate balance between the osteoblast and the osteoclast resulting in bone resorption. However, the great majority of controlled implants display a foreign body equilibrium resulting in very high survival rates of the implants over long term of follow‐up.